Viewing The Company's Commitment To Social Responsibility Based On Assets And Income - Yusuf, Sahro (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
In Indonesia, companies do not only provide benefits to their owners or investors. But also, there is a moral responsibility towards society or the surrounding environment. This happens, because a few or many companies have had a negative impact on the environment, both production waste, pollution waste, environmental damage waste, distribution waste, and so on. Therefore, social responsibility in the form of giving grants to the community from a small portion of the profits is a necessity. Based on this background, this research was conducted to be able to see the consistency of the implementation of corporate social responsibility programs towards the community as seen from the size of profits and assets. To answer these objectives, then established a quantitative research principle with regression analysis. The object of research is a leading food and beverage company in Indonesia, with a total of 36 data used and a purposive sampling technique. The results of the study explain that the size of the social responsibility fund is very dependent on the size of the assets and profits earned. Then, the asset factor that has the greatest influence on the company's CSR commitment is the amount of internal capital that generates profits. In other words, if the company benefits more from its personal assets, the profits will not be shared with other parties, so that the company is more flexible in carrying out CSR programs.